Análisis económico del sistema de producción de banano orgánico y convencional (Musa paradisiaca) en dos haciendas de la Provincia de Los Ríos. - Poveda Morán, Rubén Alexander (2019)
The cultivation of bananas planted in a traditional way has been losing in a minimum percentage hegemony to give way to an organic production that has expanded significantly due to the growth of the demand of international markets for which the present research entitled “Economic analysis of organic and conventional banana production system (Musa paradisiaca) in two farms in the province of Los Ríos ”, with the objective of calculating the production costs of organic and conventional bananas; determine the profitability of organic and conventional banana (Musa paradisiaca). Once the information from the interviews in the study farms has been analyzed, it is concluded that conventional bananas have 9,01% more bunches than organic bananas per hectare; however, the production costs of organic bananas exceed 10,86% of those of conventional bananas; It is important to emphasize that the highest profitability is obtained with the conventional production system that exceeds organic bananas by twelve percent. Keywords: organic banana, production cost, profitability.